Recursive prosodic words in Kaqchikel (Mayan). Issue 1 (1st June 2018) - Bennett, Ryan
Abstract : Following the development of Prosodic Hierarchy Theory (Selkirk 1984 ; Nespor & Vogel 1986 ), evidence has accumulated that prosodic categories may be recursively self-embedded (e.g. Selkirk 1995 ; Truckenbrodt 1999 ; Wagner 2010 ; Itô & Mester 2013, etc.). However, this conclusion is not universally accepted (e.g. Vogel 2009a ), and even the need for prosodic categories has been recently disputed (e.g. Scheer 2012b ). In this article I argue that the prefixal phonology of Kaqchikel provides clear and convincing evidence for unbounded (iterable) recursion of the prosodic word ω . Patterns of [ʔ]-insertion and degemination receive a simple, elegant treatment if recursion of the prosodic word is permitted. Theories of prosodic phonology which do without recursion are forced to resort to ad hoc stipulations to account for the same facts. Both derivational (e.g. Kiparsky 1982 ) and transderivational (e.g. Benua 2000 ) analyses of these patterns fail on morphological grounds. The overall conclusion is that both abstract prosodic structure and recursion of the prosodic word are indispensable parts of any theory of word-level phonology.